Exterior material for power storage device, method for manufacturing the same, and power storage device
A laminate exterior material for power storage devices, featuring a biomass-derived polyester heat-fusible resin layer, addresses the limitations of conventional metal materials by enabling diverse shaping and reduced weight, while reducing fossil fuel use and environmental impact.
Patent Information
- Application Number
- JP2023098043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2024-12-26
AI Technical Summary
Conventional metal exterior materials for power storage devices are difficult to shape diversely and are limited in weight reduction, failing to meet the demands of modern electronic devices that require thinner and lighter forms.
A laminate exterior material for power storage devices is developed, comprising a base material layer, a barrier layer, and a heat-fusible resin layer, where the heat-fusible resin layer is made from biomass-derived polyester, allowing for easier shaping and reduced weight.
The use of biomass-derived polyester in the heat-fusible resin layer reduces fossil fuel consumption and environmental impact while enabling the production of thinner and lighter power storage devices.
Smart Images

Figure 2024179303000005 
Figure 2024179303000006 
Figure 2024179303000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an exterior material for an electricity storage device, a manufacturing method thereof, and an electricity storage device. [Background technology]
[0002] Conventionally, various types of electricity storage devices have been developed, and in all electricity storage devices, exterior materials are essential components for sealing electricity storage device elements such as electrodes, electrolytes, etc. Conventionally, metallic exterior materials have been widely used as exterior materials for electricity storage devices.
[0003] Meanwhile, in recent years, various shapes as well as thinner and lighter weight are required for electricity storage devices along with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic exterior materials for electricity storage devices that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.
[0004] In recent years, a film-like laminate in which a base layer, a barrier layer, and a heat-sealable resin layer are laminated in this order has been proposed as an exterior material for an electricity storage device that can be easily processed into a variety of shapes and can be made thinner and lighter (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-287971 A [Patent Document 2] Special Publication No. 2002-512304 [Patent Document 3] JP 2014-12822 A Summary of the Invention [Problem to be solved by the invention]
[0006] In an exterior material for an electricity storage device constituted by the above-mentioned film-like laminate, a polyester film may be used.
[0007] Polyesters are obtained by polycondensation of diol units and dicarboxylic acid units. For example, polyethylene terephthalate (hereinafter sometimes abbreviated as PET) is produced by esterifying ethylene glycol and terephthalic acid as raw materials, followed by polycondensation. Polybutylene terephthalate (hereinafter sometimes abbreviated as PBT) is produced by esterifying 1,4-butanediol and terephthalic acid as raw materials, followed by polycondensation. These raw materials are produced from petroleum, a fossil resource. For example, ethylene glycol is industrially produced from ethylene, and terephthalic acid is industrially produced from xylene.
[0008] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the use of biomass has attracted attention. Biomass is an organic compound that is photosynthesized from carbon dioxide and water, and by using it, it becomes carbon dioxide and water again, making it a so-called carbon-neutral renewable energy. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and there are also attempts to produce polyester, a general-purpose polymer material, from these biomass raw materials.
[0009] For example, as a polyester using a biomass raw material, a polyester composed of isosorbide, which is one of the biomass raw materials, terephthalic acid, and ethylene glycol has been proposed (Patent Document 2).
[0010] In addition, biomass ethanol obtained by fermenting starch and sugars obtained from plants such as corn and sugar cane with microorganisms has been put to practical use, and ethylene glycol has also been successfully produced industrially from this biomass ethanol via ethylene.
[0011] Regarding polybutylene terephthalate using biomass raw materials, there are known methods for producing 1,4-butanediol by chemically reducing or biotechnologically hydrogenating succinic acid derived from biomass, or by producing 1,4-butanediol by direct fermentation of bacterial cells, and then polycondensing this with a dicarboxylic acid unit to produce biomass-derived polybutylene terephthalate (Patent Document 3).
[0012] A primary object of the present disclosure is to provide a novel exterior material for an electricity storage device that utilizes polyester containing raw materials derived from biomass. [Means for solving the problem]
[0013] The inventors of the present disclosure have conducted extensive research to solve the above-mentioned problems, and have found that a novel exterior material for an electricity storage device, which uses biomass-derived raw materials, can be obtained by using a polyester, at least a part of which is formed from a biomass-derived raw material, in an exterior material for an electricity storage device that is composed of a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, and which is formed from a biomass-derived raw material in the heat-sealable resin layer.
[0014] The present disclosure has been completed based on such novel findings and through further investigations. That is, the present disclosure provides the invention of the following aspects. The laminate includes, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The heat-sealable resin layer contains polyester, An exterior material for an electricity storage device, wherein at least a portion of the polyester is formed from a raw material derived from biomass. Effect of the Invention
[0015] According to the present disclosure, it is possible to provide a novel exterior material for an electricity storage device using a biomass-derived polyester. By using a biomass-derived polyester in an exterior material for an electricity storage device, it is possible to reduce the amount of fossil fuel used and to reduce the environmental load. In addition, according to the present disclosure, it is also possible to provide a manufacturing method for the exterior material for an electricity storage device, and an electricity storage device using the exterior material for an electricity storage device. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 2] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 3] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Figure 4] 1 is a schematic diagram showing an example of a cross-sectional structure of an exterior material for an electricity storage device according to the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram for illustrating a method for housing an electricity storage device element in a package formed from the exterior material for an electricity storage device of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The exterior material for an electricity storage device according to the present disclosure is a novel exterior material for an electricity storage device that is composed of a laminate including, in order from the outside, at least a base material layer, a barrier layer, and a heat-sealable resin layer, the heat-sealable resin layer containing polyester, at least a portion of which is formed from a raw material derived from biomass.
[0018] The exterior material for a power storage device of the present disclosure will be described in detail below. In this specification, the numerical range indicated by "~" means "more than or equal to" or "less than or equal to". For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less. In the numerical ranges described in the present disclosure in stages, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described in stages. In addition, the upper limit and the upper limit, the upper limit and the lower limit, or the lower limit and the lower limit, which are described separately, may be combined to form a numerical range. In addition, in the numerical ranges described in the present disclosure, the upper limit or the lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0019] 1.Laminated structure of exterior materials for energy storage devices The exterior material 10 for an electricity storage device according to the present disclosure is composed of a laminate including, from the outside, a base layer 1, a barrier layer 3, and a heat-sealable resin layer 4, in this order, as shown in FIG. 1. In the exterior material 10 for an electricity storage device, the base layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. When assembling an electricity storage device using the exterior material 10 for an electricity storage device and an electricity storage device element, the heat-sealable resin layers 4 of the exterior material 10 for an electricity storage device are placed opposite each other, and the electricity storage device element is accommodated in a space formed by heat-sealing the periphery. In the laminate constituting the exterior material 10 for an electricity storage device according to the present disclosure, the barrier layer 3 is used as a reference, and the heat-sealable resin layer 4 side is on the inner side relative to the barrier layer 3, and the base layer 1 side is on the outer side relative to the barrier layer 3.
[0020] As shown in Figures 2 to 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 2 between the base material layer 1 and the barrier layer 3, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figures 3 and 4, for example, the exterior material 10 for an electricity storage device may have an adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, for the purpose of increasing the adhesion between these layers. Also, as shown in Figure 4, a surface coating layer 6 or the like may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4 side), if necessary.
[0021] The thickness of the laminate constituting the electricity storage device exterior material 10 is not particularly limited, but from the viewpoint of cost reduction, energy density improvement, etc., examples of the thickness include about 210 μm or less, preferably about 190 μm or less, about 180 μm or less, about 155 μm or less, and about 120 μm or less. Moreover, from the viewpoint of maintaining the function of the electricity storage device exterior material 10, which is to protect the electricity storage device elements, the thickness of the laminate constituting the electricity storage device exterior material 10 is preferably about 35 μm or more, about 45 μm or more, and about 60 μm or more. Preferred ranges for the laminate constituting the exterior material 10 for electricity storage devices include, for example, about 35 to 210 μm, about 35 to 190 μm, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 210 μm, about 45 to 190 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 210 μm, about 60 to 190 μm, about 60 to 180 μm, about 60 to 155 μm, and about 60 to 120 μm. In particular, when making the electricity storage device lighter and thinner, about 60 to 155 μm is preferred, and when improving formability, about 155 to 190 μm is preferred.
[0022] In the exterior material 10 for an electricity storage device, the ratio of the total thickness of the base material layer 1, the adhesive layer 2 provided as needed, the barrier layer 3, the adhesive layer 5 provided as needed, the heat-sealable resin layer 4, and the surface coating layer 6 provided as needed to the thickness (total thickness) of the laminate constituting the exterior material 10 for an electricity storage device is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. As a specific example, when the exterior material 10 for an electricity storage device of the present disclosure includes the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, and the heat-sealable resin layer 4, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior material 10 for an electricity storage device is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. Furthermore, even when the exterior packaging material 10 for an electricity storage device of the present disclosure is a laminate including a substrate layer 1, an adhesive layer 2, a barrier layer 3, and a heat-sealable resin layer 4, the ratio of the total thickness of these layers to the thickness (total thickness) of the laminate constituting the exterior packaging material 10 for an electricity storage device can be, for example, 80% or more, preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more.
[0023] 2. Each layer that forms the exterior material for electricity storage devices [Base material layer 1] In the present disclosure, the substrate layer 1 is a layer provided for the purpose of exhibiting the function as a substrate of the exterior material for an electricity storage device, etc. The substrate layer 1 is located on the outer layer side of the exterior material for an electricity storage device.
[0024] The material forming the base layer 1 is not particularly limited as long as it has the function of a base, that is, at least insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described later.
[0025] When the substrate layer 1 is formed of a resin, the substrate layer 1 can be formed of, for example, a resin film. When the substrate layer 1 is formed of a resin film, a preformed resin film may be used as the substrate layer 1 when the substrate layer 1 is laminated with the barrier layer 3 or the like to manufacture the exterior material for an electricity storage device 10 of the present disclosure. In addition, the resin forming the substrate layer 1 may be formed into a film on the surface of the barrier layer 3 or the like by extrusion molding, coating, or the like to form the substrate layer 1 formed of a resin film. The resin film may be an unstretched film or a stretched film. Examples of the stretched film include a uniaxially stretched film and a biaxially stretched film, and a biaxially stretched film is preferable. Examples of the stretching method for forming a biaxially stretched film include a sequential biaxial stretching method, an inflation method, and a simultaneous biaxial stretching method. Examples of the method for applying the resin include a roll coating method, a gravure coating method, and an extrusion coating method.
[0026] Examples of the resin forming the base layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, and phenol resin, as well as modified versions of these resins. The resin forming the base layer 1 may be a copolymer of these resins or a modified version of the copolymer. Furthermore, it may be a mixture of these resins.
[0027] The base layer 1 preferably contains these resins as the main component, and more preferably contains polyester or polyamide as the main component. Here, the main component means that the content of the resin components contained in the base layer 1 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more. For example, the base layer 1 contains polyester or polyamide as the main component means that the content of polyester or polyamide among the resin components contained in the base layer 1 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.
[0028] Of these, preferred examples of the resin forming the base layer 1 include polyester and polyamide.
[0029] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters. Examples of copolymerized polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit. Specific examples of polyesters include copolymerized polyesters in which ethylene terephthalate is the main repeating unit and is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), and polyethylene (terephthalate / decane dicarboxylate). These polyesters may be used alone or in combination of two or more.
[0030] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) that contain structural units derived from terephthalic acid and / or isophthalic acid, and polyamides containing aromatic compounds such as polyamide MXD6 (polymetaxylylene adipamide); alicyclic polyamides such as polyamide PACM6 (polybis(4-aminocyclohexyl)methane adipamide); polyamides copolymerized with a lactam component or an isocyanate component such as 4,4'-diphenylmethane diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers that are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and polyamides such as copolymers of these copolymers. These polyamides may be used alone or in combination of two or more.
[0031] The base layer 1 preferably includes at least one of a polyester film, a polyamide film, and a polyolefin film, preferably includes at least one of a stretched polyester film, a stretched polyamide film, and a stretched polyolefin film, more preferably includes at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film, and a stretched polypropylene film, and even more preferably includes at least one of a biaxially oriented polyethylene terephthalate film, a biaxially oriented polybutylene terephthalate film, a biaxially oriented nylon film, and a biaxially oriented polypropylene film.
[0032] The base layer 1 may be a single layer, or may be composed of two or more layers. When the base layer 1 is composed of two or more layers, the base layer 1 may be a laminate in which resin films are laminated with an adhesive or the like, or may be a laminate of resin films in which resins are co-extruded to form two or more layers. In addition, a laminate of resin films in which resins are co-extruded to form two or more layers may be used as the base layer 1 without being stretched, or may be uniaxially or biaxially stretched to form the base layer 1.
[0033] In the base layer 1, specific examples of the laminate of two or more resin films include a laminate of a polyester film and a nylon film, a laminate of two or more nylon films, and a laminate of two or more polyester films, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more stretched nylon films, and a laminate of two or more stretched polyester films. For example, when the base layer 1 is a laminate of two resin films, a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film is preferred, and a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film is more preferred. In addition, when the base layer 1 is a laminate of two or more resin films, it is preferable that the polyester resin film is located in the outermost layer of the base layer 1, because the polyester resin is less likely to discolor when, for example, an electrolyte is attached to the surface.
[0034] When the base layer 1 is a laminate of two or more resin films, the two or more resin films may be laminated via an adhesive. Examples of preferred adhesives include the same adhesives as those exemplified in the adhesive layer 2 described below. The method for laminating two or more resin films is not particularly limited, and a known method can be adopted, such as a dry lamination method, a sandwich lamination method, an extrusion lamination method, a thermal lamination method, etc., and preferably a dry lamination method. When laminating by the dry lamination method, it is preferable to use a polyurethane adhesive as the adhesive. In this case, the thickness of the adhesive is, for example, about 2 to 5 μm. Also, an anchor coat layer may be formed on the resin film and laminated. Examples of the anchor coat layer include the same adhesives as those exemplified in the adhesive layer 2 described below. In this case, the thickness of the anchor coat layer is, for example, about 0.01 to 1.0 μm.
[0035] Furthermore, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the interior of the base layer 1. The additives may be used alone or in combination of two or more.
[0036] In the present disclosure, from the viewpoint of improving the moldability of the exterior material for a power storage device, it is preferable that a lubricant is present on at least one of the surface and the inside of the base material layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, and N,N'-distearylisophthalic acid amide.The lubricant may be used alone or in combination of two or more kinds, and it is preferable to use a combination of two or more kinds.
[0037] When a lubricant is present on the surface of the base layer 1, the amount of the lubricant is not particularly limited, but may be, for example, about 3 mg / m 2 or more, preferably about 4 mg / m 2 More than about 5mg / m 2 The amount of lubricant present on the surface of the base layer 1 is, for example, about 15 mg / m 2 Less than or equal to about 14 mg / m 2 Below, about 10mg / m 2 The preferred range of the amount of lubricant present on the surface of the base layer 1 is 3 to 15 mg / m 2 degree, 3~14mg / m 2 degree, 3~10mg / m 2 degree, 4~15mg / m 2 degree, 4~14mg / m 2 degree, 4~10mg / m 2 degree, 5~15mg / m 2 degree, 5~14mg / m 2 degree, 5~10mg / m 2 The degree of
[0038] The lubricant present on the surface of the base layer 1 may be a lubricant exuded from the resin constituting the base layer 1, or a lubricant applied to the surface of the base layer 1.
[0039] The thickness of the substrate layer 1 is not particularly limited as long as it functions as a substrate, and may be, for example, about 3 μm or more, preferably about 10 μm or more. The thickness of the substrate layer 1 may be, for example, about 50 μm or less, preferably about 35 μm or less, 11 μm or less, or 8 μm or less. The preferred range of the thickness of the substrate layer 1 may be about 3 to 50 μm, about 3 to 35 μm, about 3 to 11 μm, about 3 to 8 μm, about 10 to 50 μm, or about 10 to 35 μm. In particular, when making the electric storage device lighter and thinner, about 3 to 35 μm, about 3 to 11 μm, or about 3 to 8 μm is preferred, and when improving the formability, about 35 to 50 μm is preferred. When the substrate layer 1 is a laminate of two or more resin films, the thickness of each resin film constituting each layer is not particularly limited, and may be, for example, about 2 μm or more, preferably about 10 μm or more, or about 18 μm or more. The thickness of the resin film constituting each layer is, for example, about 33 μm or less, preferably about 28 μm or less, about 23 μm or less, about 18 μm or less, 11 μm or less, or 8 μm or less. Preferred ranges of the thickness of the resin film constituting each layer include about 2 to 33 μm, about 2 to 28 μm, about 2 to 23 μm, about 2 to 18 μm, about 2 to 11 μm, about 2 to 8 μm, about 10 to 33 μm, about 10 to 28 μm, about 10 to 23 μm, about 10 to 18 μm, about 18 to 33 μm, about 18 to 28 μm, or about 18 to 23 μm.
[0040] [Adhesive layer 2] In the exterior material for an electricity storage device of the present disclosure, the adhesive layer 2 is a layer that is provided between the base layer 1 and the barrier layer 3 as necessary for the purpose of increasing the adhesion between them.
[0041] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any of a chemical reaction type, a solvent volatilization type, a hot melt type, a hot pressure type, etc. Also, it may be a two-component curing adhesive (two-component adhesive), a one-component curing adhesive (one-component adhesive), or a resin that does not involve a curing reaction. Also, the adhesive layer 2 may be a single layer or multiple layers.
[0042] Specific examples of adhesive components contained in the adhesive include polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyesters; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolymerized polyamides; polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth)acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferred. In addition, the adhesive strength of these adhesive component resins can be increased by using an appropriate curing agent in combination. The curing agent is selected from polyisocyanates, multifunctional epoxy resins, oxazoline group-containing polymers, polyamine resins, acid anhydrides, and the like, depending on the functional groups of the adhesive components.
[0043] Examples of polyurethane adhesives include polyurethane adhesives containing a first agent containing a polyol compound and a second agent containing an isocyanate compound. A two-liquid curing type polyurethane adhesive is preferably used, in which a polyol such as polyester polyol, polyether polyol, and acrylic polyol is used as the first agent, and an aromatic or aliphatic polyisocyanate is used as the second agent. Examples of polyurethane adhesives include polyurethane adhesives containing a polyurethane compound in which a polyol compound and an isocyanate compound have been reacted in advance, and an isocyanate compound. Examples of polyurethane adhesives include polyurethane adhesives containing a polyurethane compound in which a polyol compound and an isocyanate compound have been reacted in advance, and a polyol compound. Examples of polyurethane adhesives include polyurethane adhesives in which a polyurethane compound in which a polyol compound and an isocyanate compound have been reacted in advance is cured by reacting it with moisture in the air or the like. As the polyol compound, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit. Examples of the second agent include aliphatic, alicyclic, aromatic, and araliphatic isocyanate compounds. Examples of isocyanate compounds include hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI), isophorone diisocyanate (IPDI), hydrogenated XDI (H6XDI), hydrogenated MDI (H12MDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and naphthalene diisocyanate (NDI). In addition, examples include polyfunctional isocyanate modified products of one or more of these diisocyanates. In addition, a polymer (e.g., a trimer) can also be used as the polyisocyanate compound. Examples of such polymers include adducts, biuret bodies, and nurate bodies. Since the adhesive layer 2 is formed from a polyurethane adhesive, excellent electrolyte resistance is imparted to the exterior material for an electricity storage device, and peeling of the base material layer 1 is suppressed even if the electrolyte adheres to the side surface.
[0044] In addition, the adhesive layer 2 is allowed to contain other components as long as they do not impair adhesion, and may contain a colorant, a thermoplastic elastomer, a tackifier, a filler, etc. By containing a colorant in the adhesive layer 2, the exterior material for a power storage device can be colored. As the colorant, known colorants such as pigments and dyes can be used. In addition, only one type of colorant may be used, or two or more types may be mixed and used.
[0045] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo-based, phthalocyanine-based, quinacridone-based, anthraquinone-based, dioxazine-based, indigothioindigo-based, perinone-perylene-based, isoindolenine-based, and benzimidazolone-based pigments, while examples of inorganic pigments include carbon black-based, titanium oxide-based, cadmium-based, lead-based, chromium oxide-based, and iron-based pigments, and other examples include fine powder of mica, fish scale foil, and the like.
[0046] Among colorants, carbon black is preferred in order to give the exterior material for an electricity storage device a black appearance, for example.
[0047] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0048] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the exterior material for an electricity storage device is colored, and is, for example, about 5 to 60 mass %, preferably 10 to 40 mass %.
[0049] The thickness of the adhesive layer 2 is not particularly limited as long as it can bond the base layer 1 and the barrier layer 3, but is, for example, about 1 μm or more, about 2 μm or more. The thickness of the adhesive layer 2 is, for example, about 10 μm or less, about 5 μm or less. Preferable ranges for the thickness of the adhesive layer 2 include about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0050] [Colored layer] The colored layer is a layer that is provided between the base material layer 1 and the barrier layer 3 as necessary (not shown). When the adhesive layer 2 is provided, a colored layer may be provided between the base material layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. Also, a colored layer may be provided on the outside of the base material layer 1. By providing a colored layer, the exterior material for an electricity storage device can be colored.
[0051] The colored layer can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1 or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.
[0052] Specific examples of the colorant contained in the colored layer include the same as those exemplified in the section [Adhesive layer 2].
[0053] [Barrier layer 3] In the packaging material for an electricity storage device, the barrier layer 3 is a layer that at least prevents the penetration of moisture.
[0054] Examples of the barrier layer 3 include metal foils, vapor-deposited films, and resin layers having barrier properties. Examples of the vapor-deposited films include metal vapor-deposited films, inorganic oxide vapor-deposited films, and carbon-containing inorganic oxide vapor-deposited films. Examples of the resin layer include fluorine-containing resins such as polyvinylidene chloride, polymers mainly composed of chlorotrifluoroethylene (CTFE), polymers mainly composed of tetrafluoroethylene (TFE), polymers having fluoroalkyl groups, and polymers mainly composed of fluoroalkyl units, and ethylene-vinyl alcohol copolymers. Examples of the barrier layer 3 include resin films having at least one of these vapor-deposited films and resin layers. The barrier layer 3 may be provided in a plurality of layers. The barrier layer 3 preferably includes a layer made of a metal material. Specific examples of the metal material constituting the barrier layer 3 include aluminum alloys, stainless steel, titanium steel, and steel plates. When used as a metal foil, the barrier layer 3 preferably includes at least one of aluminum alloy foil and stainless steel foil.
[0055] From the viewpoint of improving the formability of the exterior material for a power storage device, the aluminum alloy foil is preferably a soft aluminum alloy foil made of, for example, an annealed aluminum alloy, and from the viewpoint of further improving the formability, the aluminum alloy foil is preferably an iron-containing aluminum alloy foil. In the iron-containing aluminum alloy foil (100 mass%), the iron content is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%. By making the iron content 0.1 mass% or more, an exterior material for a power storage device having better formability can be obtained. By making the iron content 9.0 mass% or less, an exterior material for a power storage device having better flexibility can be obtained. Examples of the soft aluminum alloy foil include aluminum alloy foils having a composition specified in JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, or JIS H4000:2014 A8079P-O. Silicon, magnesium, copper, manganese, etc. may be added as necessary. Softening can be performed by annealing or the like.
[0056] Examples of the stainless steel foil include austenitic, ferritic, austenitic-ferritic, martensitic, and precipitation hardened stainless steel foils. From the viewpoint of providing an exterior material for an electricity storage device having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0057] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred.
[0058] In the case of a metal foil, the thickness of the barrier layer 3 is sufficient as long as it at least functions as a barrier layer that prevents moisture from penetrating, and may be, for example, about 9 to 200 μm. The thickness of the barrier layer 3 is preferably about 85 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, and particularly preferably about 35 μm or less. The thickness of the barrier layer 3 is preferably about 10 μm or more, even more preferably about 20 μm or more, and more preferably about 25 μm or more. The preferred ranges of the thickness of the barrier layer 3 include about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is made of an aluminum alloy foil, the above-mentioned range is particularly preferable. From the viewpoint of imparting high formability and high rigidity to the exterior packaging material 10 for an electric storage device, the thickness of the barrier layer 3 is preferably about 35 μm or more, more preferably about 45 μm or more, even more preferably about 50 μm or more, and even more preferably about 55 μm or more, and is preferably about 200 μm or less, more preferably about 85 μm or less, even more preferably about 75 μm or less, and even more preferably about 70 μm or less. Preferred ranges are about 35 to 200 μm, about 35 to 85 μm, about 35 to 75 μm, about 35 to 70 μm, about 45 to 200 μm, about 45 to 85 μm, about 45 to 75 μm, about 45 to 70 μm, about 50 to 200 μm, about 50 to 85 μm, about 50 to 75 μm, about 50 to 70 μm, about 55 to 200 μm, about 55 to 85 μm, about 55 to 75 μm, and about 55 to 70 μm. The high formability of the exterior material 10 for an electricity storage device makes deep drawing easy, which can contribute to increasing the capacity of the electricity storage device. In addition, when the capacity of the electricity storage device is increased, the weight of the electricity storage device increases, but the increased rigidity of the exterior material 10 for an electricity storage device can contribute to high sealing performance of the electricity storage device.In particular, when the barrier layer 3 is made of stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, even more preferably about 40 μm or less, even more preferably about 30 μm or less, and particularly preferably about 25 μm or less. The thickness of the stainless steel foil is preferably about 10 μm or more, more preferably about 15 μm or more. Preferred ranges of the thickness of the stainless steel foil include about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm.
[0059] In addition, when the barrier layer 3 is a metal foil, it is preferable to provide a corrosion-resistant film at least on the surface opposite to the base layer in order to prevent dissolution and corrosion. The barrier layer 3 may be provided with a corrosion-resistant film on both sides. Here, the corrosion-resistant film refers to a thin film that is provided with corrosion resistance (e.g., acid resistance, alkali resistance, etc.) on the surface of the barrier layer by performing, for example, hydrothermal conversion treatment such as boehmite treatment, chemical conversion treatment, anodizing treatment, plating treatment such as nickel or chromium, or corrosion prevention treatment by applying a coating agent. Specifically, the corrosion-resistant film means a film that improves the acid resistance of the barrier layer (acid-resistant film), a film that improves the alkali resistance of the barrier layer (alkali-resistant film), etc. As a treatment for forming a corrosion-resistant film, one type may be performed, or two or more types may be combined. In addition, not only one layer but also multiple layers may be formed. Furthermore, among these treatments, the hydrothermal conversion treatment and the anodizing treatment are treatments in which the metal foil surface is dissolved by a treatment agent to form a metal compound with excellent corrosion resistance. These treatments may be included in the definition of “chemical conversion treatment.” In addition, when the barrier layer 3 has a corrosion-resistant coating, the barrier layer 3 includes the corrosion-resistant coating.
[0060] The corrosion-resistant coating prevents delamination between a barrier layer (e.g., an aluminum alloy foil) and a base layer during molding of an exterior material for an electricity storage device, prevents dissolution and corrosion of the barrier layer surface due to hydrogen fluoride produced by a reaction between an electrolyte and moisture, and in particular prevents dissolution and corrosion of aluminum oxide present on the barrier layer surface when the barrier layer is an aluminum alloy foil, and also improves the adhesion (wettability) of the barrier layer surface, thereby preventing delamination between the base layer and the barrier layer during heat sealing and between the base layer and the barrier layer during molding.
[0061] Various corrosion-resistant films formed by chemical conversion treatments are known, and mainly include corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds, and rare earth oxides. Examples of chemical conversion treatments using phosphates and chromates include chromate chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, and chromate treatment. Examples of chromium compounds used in these treatments include chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate. Examples of phosphorus compounds used in these treatments include sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid. Examples of chromate treatments include etching chromate treatment, electrolytic chromate treatment, and coating-type chromate treatment, and coating-type chromate treatment is preferred. In this coating type chromate treatment, at least the inner layer side of the barrier layer (e.g., aluminum alloy foil) is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is coated with a treatment liquid mainly composed of a metal phosphate such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, or Zn (zinc) phosphate, or a mixture of these metal salts, or a treatment liquid mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid consisting of a mixture of these with a synthetic resin, or the like, by a known coating method such as a roll coating method, a gravure printing method, or a dipping method, and then dried. As the treatment liquid, various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents can be used, and water is preferred. Examples of the resin component used here include polymers such as phenolic resins and acrylic resins, and chromate treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylic acid ester copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or a derivative thereof such as sodium salt, ammonium salt, or amine salt. In particular, a derivative of polyacrylic acid such as an ammonium salt, sodium salt, or amine salt of polyacrylic acid is preferable. In the present disclosure, polyacrylic acid means a polymer of acrylic acid. The acrylic resin is also preferably a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride, and is also preferably an ammonium salt, sodium salt, or amine salt of a copolymer of acrylic acid and dicarboxylic acid or dicarboxylic acid anhydride. Only one type of acrylic resin may be used, or two or more types may be mixed and used.
[0062] [ka]
[0063] [ka]
[0064] [ka]
[0065] [ka]
[0066] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) to (4) include linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the following formulae may be the same or different. In the general formulae (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the general formulae (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000. The aminated phenol polymer can be prepared, for example, by polycondensing a phenol compound or a naphthol compound with formaldehyde to produce a polymer consisting of the repeating units represented by the above general formula (1) or (3), and then polycondensing the polymer with formaldehyde and an amine (R 1 R 2 NH) to the functional group (-CHNR 1 R 2 The aminated phenol polymers can be used alone or in combination of two or more.
[0067] Another example of the corrosion-resistant film is a thin film formed by a coating-type corrosion prevention treatment in which a coating agent containing at least one selected from the group consisting of rare earth element oxide sol, anionic polymer, and cationic polymer is applied. The coating agent may further contain phosphoric acid or a phosphate, and a crosslinking agent for crosslinking the polymer. The rare earth element oxide sol has rare earth element oxide fine particles (for example, particles with an average particle size of 100 nm or less) dispersed in a liquid dispersion medium. Examples of rare earth element oxides include cerium oxide, yttrium oxide, neodymium oxide, and lanthanum oxide, and cerium oxide is preferred from the viewpoint of further improving adhesion. The rare earth element oxide contained in the corrosion-resistant film can be used alone or in combination of two or more. Examples of the liquid dispersion medium for the rare earth element oxide sol include various solvents such as water, alcohol-based solvents, hydrocarbon-based solvents, ketone-based solvents, ester-based solvents, and ether-based solvents, and water is preferred. As the cationic polymer, for example, polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or its derivative, aminated phenol, etc. are preferable. In addition, as the anionic polymer, poly(meth)acrylic acid or its salt, or a copolymer mainly composed of (meth)acrylic acid or its salt, is preferable. In addition, it is preferable that the crosslinking agent is at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. In addition, it is preferable that the phosphoric acid or the phosphoric acid salt is a condensed phosphoric acid or a condensed phosphate salt.
[0068] One example of a corrosion-resistant coating is one formed by applying a solution of fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate dispersed in phosphoric acid to the surface of a barrier layer and baking the coating at 150°C or higher.
[0069] If necessary, the corrosion-resistant coating may have a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and anionic polymer include those mentioned above.
[0070] The composition of the corrosion-resistant film can be analyzed by, for example, time-of-flight secondary ion mass spectrometry.
[0071] The amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of coating-type chromate treatment, the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 is preferably 1 mm. 2 It is desirable that the chromate compound is contained in an amount, calculated as chromium, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, the phosphorus compound is contained in an amount, calculated as phosphorus, of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, and the aminated phenol polymer is contained in an amount, calculated as phosphorus, of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, per unit weight of the ink.
[0072] The thickness of the corrosion-resistant film is not particularly limited, but is preferably about 1 nm to 20 μm, more preferably about 1 nm to 100 nm, and even more preferably about 1 nm to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the barrier layer and the heat-sealable resin layer. The thickness of the corrosion-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy. Analysis of the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry can reveal that, for example, secondary ions consisting of Ce, P, and O (e.g., Ce2PO4 + , CePO4 - At least one of the following: CrPO2 + , CrPO4 - Peaks derived from at least one of the above are detected.
[0073] The chemical conversion treatment is carried out by applying a solution containing a compound used for forming a corrosion-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer becomes about 70 to 200°C. In addition, before applying the chemical conversion treatment to the barrier layer, the barrier layer may be subjected to a degreasing treatment by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, it becomes possible to carry out the chemical conversion treatment of the surface of the barrier layer more efficiently. In addition, by using an acid degreasing agent in which a fluorine-containing compound is dissolved in an inorganic acid for the degreasing treatment, it is possible to not only degrease the metal foil but also form a fluoride of the metal that is in a passive state, and in such a case, only the degreasing treatment may be carried out.
[0074] [Thermal adhesive resin layer 4] In the exterior packaging material for an electricity storage device of the present disclosure, the heat-sealable resin layer 4 corresponds to the innermost layer and is a layer (sealant layer) that exhibits the function of sealing the electricity storage device elements by heat-sealing the heat-sealable resin layers to each other when the electricity storage device is assembled.
[0075] In the present disclosure, the thermally adhesive resin layer 4 contains polyester, and at least a part of the polyester is formed from a raw material derived from biomass. Hereinafter, the polyester at least a part of which is formed from a raw material derived from biomass may be referred to as "polyester A".
[0076] (Polyester A) In the polyester A, at least one of the diol unit (diol residue) and the dicarboxylic acid unit (dicarboxylic acid residue) is derived from biomass. For example, the diol unit is an alkylene glycol derived from biomass, and the dicarboxylic acid unit is a dicarboxylic acid derived from fossil fuel. Such a polyester A is obtained by a polycondensation reaction of the diol unit, which is an alkylene glycol derived from biomass, and the dicarboxylic acid unit, which is a dicarboxylic acid derived from fossil fuel.
[0077] Biomass-derived alkylene glycol is made from alcohol (e.g., biomass ethanol, etc.) produced from biomass as a raw material. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. Commercially available biomass ethylene glycol may also be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.
[0078] Examples of the biomass-derived alkylene glycol include aliphatic diols derived from biomass, the lower limit of which is 2 or more and the upper limit of which is usually 10 or less, preferably 6 or less. Specific examples include ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, decamethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, which are derived from biomass. These may be used alone or as a mixture of two or more. Among these, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, and 1,4-cyclohexanedimethanol, which are derived from biomass, are preferred, and ethylene glycol derived from biomass is particularly preferred. For example, when ethylene glycol derived from biomass is used as a raw material for polyester, polyethylene terephthalate is obtained using a raw material derived from biomass. Also, when 1,4-butanediol derived from biomass is used as a raw material for polyester, polybutylene terephthalate is obtained using a raw material derived from biomass.
[0079] The dicarboxylic acid unit of polyester A uses at least one of a biomass-derived dicarboxylic acid and a fossil fuel-derived dicarboxylic acid. As the dicarboxylic acid, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and their derivatives can be used without limitation. As the aromatic dicarboxylic acid, terephthalic acid and isophthalic acid can be mentioned, and as the derivative of aromatic dicarboxylic acid, lower alkyl ester of aromatic dicarboxylic acid, specifically, methyl ester, ethyl ester, propyl ester, butyl ester, etc. can be mentioned. Among them, terephthalic acid is preferable, and as the derivative of aromatic dicarboxylic acid, dimethyl terephthalate is preferable.
[0080] In addition, specific examples of the aliphatic dicarboxylic acid include linear or alicyclic dicarboxylic acids having 2 to 40 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. In addition, examples of the derivatives of the aliphatic dicarboxylic acids include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above aliphatic dicarboxylic acids, and cyclic acid anhydrides of the above aliphatic dicarboxylic acids, such as succinic anhydride. Among these, adipic acid, succinic acid, dimer acid, or a mixture thereof is preferred, and those containing succinic acid as the main component are particularly preferred. As the derivatives of the aliphatic dicarboxylic acid, methyl esters of adipic acid and succinic acid, or a mixture thereof, are more preferred.
[0081] These dicarboxylic acids may be used alone or in combination of two or more.
[0082] The polyester A may be a copolymer polyester in which a copolymer component is added as a third component in addition to the above diol component and dicarboxylic acid component. Specific examples of the copolymer component include bifunctional oxycarboxylic acid, and at least one polyfunctional compound selected from the group consisting of trifunctional or more polyhydric alcohols, trifunctional or more polyvalent carboxylic acids and / or their anhydrides, and trifunctional or more oxycarboxylic acids to form a crosslinked structure. Among these copolymer components, bifunctional and / or trifunctional or more oxycarboxylic acids are particularly preferably used because they tend to easily produce copolymer polyesters with a high degree of polymerization. Among them, the use of trifunctional or more oxycarboxylic acids is most preferred because a polyester with a high degree of polymerization can be easily produced with a very small amount without using a chain extender described later.
[0083] Polyester A may also be a high molecular weight polyester obtained by chain-extending (coupling) these copolymer polyesters. As the chain extender, a carbonate compound, a diisocyanate compound or the like may be used, and the amount thereof is usually 10 mol % or less, preferably 5 mol % or less, more preferably 3 mol % or less of carbonate bonds and urethane bonds relative to 100 mol % of all monomer units constituting polyester A.
[0084] Specific examples of carbonate compounds include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds composed of the same or different hydroxy compounds derived from hydroxy compounds such as phenols and alcohols can be used.
[0085] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.
[0086] The polyester A can be obtained by a conventionally known method of polycondensing the above-mentioned diol unit and dicarboxylic acid unit. Specifically, the polyester A can be produced by a general melt polymerization method in which an esterification reaction and / or an ester exchange reaction between the above-mentioned dicarboxylic acid component and the diol component is carried out, followed by a polycondensation reaction under reduced pressure, or a known solution heating dehydration condensation method using an organic solvent.
[0087] The amount of diol used in producing polyester A is substantially equimolar to 100 moles of dicarboxylic acid or a derivative thereof. Generally, however, distillate is generated during the esterification and / or transesterification reaction and / or condensation polymerization reaction, so that an excess of 0.1 to 20 mol % is used.
[0088] The polycondensation reaction is preferably carried out in the presence of a polymerization catalyst. The timing of adding the polymerization catalyst is not particularly limited as long as it is before the polycondensation reaction, and the catalyst may be added when the raw materials are charged or when the pressure reduction is started.
[0089] The polymerization catalyst generally includes compounds containing metal elements of Groups 1 to 14 of the periodic table, excluding hydrogen and carbon. Specifically, compounds containing organic groups such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts containing at least one metal selected from the group consisting of titanium, zirconium, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, and potassium, and further inorganic compounds such as oxides and halides of the above metals and mixtures thereof. Among these, metal compounds containing titanium, zirconium, germanium, zinc, aluminum, magnesium, and calcium, and mixtures thereof are preferred, and titanium compounds, zirconium compounds, and germanium compounds are particularly preferred. In addition, the catalyst is preferably a compound that is liquid during polymerization or dissolves in an ester oligomer or polyester, because the polymerization rate increases when the catalyst is in a molten or dissolved state during polymerization.
[0090] As the titanium compound, tetraalkyl titanate is preferred, specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof can be mentioned. In addition, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium (diisopropoxide) acetylacetonate, titanium bis (ammonium lactate) dihydroxide, titanium bis (ethylacetoacetate) diisopropoxide, titanium (triethanolamine) isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolamine, butyl titanate dimer, etc. can also be preferably used. Furthermore, titanium oxide and composite oxides containing titanium and silicon can also be preferably used. Among these, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, butyl titanate dimer, titanium oxide, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis_Industrial_Fibers) are preferred, and tetra-n-butyl titanate, polyhydroxytitanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and titania / silica composite oxide (e.g., product name: C-94 manufactured by Acordis_Industrial_Fibers) are particularly preferred.
[0091] Specific examples of the zirconium compound include zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof. Zirconium oxide and composite oxides containing, for example, zirconium and silicon may also be used. Among these, zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide are preferred.
[0092] Specific examples of germanium compounds include inorganic germanium compounds such as germanium oxide and germanium chloride, and organic germanium compounds such as tetraalkoxygermanium. In view of cost and availability, germanium oxide, tetraethoxygermanium, and tetrabutoxygermanium are preferred, with germanium oxide being particularly preferred.
[0093] When using metal compounds as these polymerization catalysts, the amount of catalyst used is usually 5 ppm or more, preferably 10 ppm or more, and the upper limit is usually 30,000 ppm or less, preferably 1,000 ppm or less, more preferably 250 ppm or less, and particularly preferably 130 ppm or less, as the amount of metal relative to the polyester A produced. If the amount of catalyst used is too large, not only is it economically disadvantageous but also the thermal stability of the polymer is reduced, whereas if the amount is too small, the polymerization activity is reduced, and accordingly the decomposition of the polymer is easily induced during the polymer production. As for the amount of catalyst used here, the method of reducing the amount of catalyst used is a preferred embodiment, since the amount of terminal carboxyl groups of the polyester A produced is reduced as the amount of catalyst used is reduced.
[0094] The reaction temperature of the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually in the range of 150 to 260° C., and the reaction atmosphere is usually an inert gas atmosphere such as nitrogen or argon, etc. The reaction pressure is usually normal pressure to 10 kPa, and the reaction time is usually about 1 hour to 10 hours.
[0095] In the above-mentioned production process, a chain extender (coupling agent) may be added to the reaction system. The chain extender is added to the reaction system in a homogeneous molten state without a solvent after the completion of polycondensation, and reacted with the polyester obtained by polycondensation.
[0096] The high molecular weight polyester using these chain extenders (coupling agents) can be produced by using known techniques. After the polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without a solvent, and reacted with the polyester obtained by the polycondensation. Specifically, a polyester resin having a higher molecular weight can be obtained by reacting the chain extender with a polyester prepolymer obtained by catalytic reaction of a diol with a dicarboxylic acid, which has a terminal group substantially having a hydroxyl group and has a mass average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more. If the prepolymer has a mass average molecular weight of 20,000 or more, a small amount of coupling agent is used, and since it is not affected by the remaining catalyst even under harsh conditions such as a molten state, a high molecular weight polyester A can be produced without generating gel during the reaction.
[0097] The obtained polyester A may be solidified and then subjected to solid-phase polymerization as necessary to further increase the degree of polymerization or to remove oligomers such as cyclic trimers. Specifically, the polyester is chipped and dried, and then pre-crystallized by heating at a temperature of 100 to 180°C for about 1 to 8 hours, and then heated at a temperature of 190 to 230°C under an inert gas flow or under reduced pressure for 1 to several tens of hours.
[0098] The intrinsic viscosity of the polyester A obtained as described above (measured in an orthochlorophenol solution at 35°C) is preferably 0.5 dl / g to 1.5 dl / g, more preferably 0.6 dl / g to 1.2 dl / g. If the intrinsic viscosity is less than 0.5 dl / g, the mechanical properties required for the polyester film used as the base layer of the exterior material for the power storage device, including tear strength, may be insufficient. On the other hand, if the intrinsic viscosity exceeds 1.5 dl / g, the productivity in the raw material production process and the film formation process is impaired.
[0099] In the production process of polyester A, or to the produced polyester A, various additives may be added within a range that does not impair its properties, such as plasticizers, UV stabilizers, coloring inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducing agents, release agents, antioxidants, ion exchange agents, coloring pigments, etc. These additives are added in an amount of preferably 5% by mass or more, more preferably 5 to 50% by mass, and even more preferably 5 to 20% by mass, based on the entire resin composition that forms the heat-fusible resin layer 4.
[0100] In order to more suitably exert the effects of the present disclosure, the content of polyester A in the resin composition forming the heat-sealable resin layer 4 is preferably 50% by mass or more, more preferably 50 to 95% by mass, and even more preferably 50 to 90% by mass.
[0101] (Polyester B) In the present disclosure, the thermally adhesive resin layer 4 may further contain, in addition to the polyester A, a polyester B which is a polyester using recycled raw materials (hereinafter also referred to as recycled polyester). The polyester B is a polyester obtained by recycling a resin product made of a polyester in which the diol unit is a diol derived from a fossil fuel or an alkylene glycol derived from a biomass, and the dicarboxylic acid unit is a dicarboxylic acid derived from a fossil fuel. The polyester B is a polyester obtained by recycling a product made of a polyester resin obtained by a polycondensation reaction using a diol unit in which the diol unit is a diol derived from a fossil fuel or an ethylene glycol derived from a biomass, and a dicarboxylic acid unit in which the dicarboxylic acid unit is a dicarboxylic acid derived from a fossil fuel.
[0102] The resin that is the basis of the recycled polyester (that is, the polyester resin before recycling) may be one in which both the diol unit and the dicarboxylic acid unit are made from raw materials derived from fossil fuels, or may be the biomass polyester described above.
[0103] Examples of the diol derived from fossil fuels used in the resin that is the basis of the recycled polyester include aliphatic diols, aromatic diols, and derivatives thereof, and those used as diol units in conventional polyesters can be suitably used. The aliphatic diol is not particularly limited as long as it is an aliphatic or alicyclic compound having two OH groups, but examples of the aliphatic diol include aliphatic diols having a carbon number of 2 or more and usually 10 or less, preferably 6 or less. Specific examples include ethylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,6-hexamethylene glycol, decamethylene glycol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. These may be used alone or in a mixture of two or more. Among these, ethylene glycol, 1,4-butanediol, 1,3-propylene glycol, and 1,4-cyclohexanedimethanol are preferred, and ethylene glycol and 1,4-butanediol are particularly preferred.
[0104] In order to more suitably exert the effects of the present disclosure, the content of polyester B in the resin composition forming the heat-sealable resin layer 4 is preferably 50 mass % or less, more preferably 5 to 45 mass %, and even more preferably 5 to 40 mass %.
[0105] In the present disclosure, it is preferable that each of the polyester A and the polyester B is polybutylene terephthalate. The dicarboxylic acid component constituting the dicarboxylic acid residue of the polybutylene terephthalate contains terephthalic acid, and may contain other aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids as necessary. The dicarboxylic acid component may be an ester-forming derivative of these dicarboxylic acid components. The dicarboxylic acid component may be only one type A, or may be two or more types. These dicarboxylic acid components may be derived from either fossil fuels or biomass.
[0106] In polybutylene terephthalate, examples of other aromatic dicarboxylic acids include isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, bis(p-carboxyphenyl)methane, anthracene dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, and 5-sodium sulfoisophthalic acid. Examples of ester-forming derivatives of terephthalic acid or other aromatic dicarboxylic acids include terephthalic acid and lower alkyl esters of the aromatic dicarboxylic acids. More specifically, examples of such derivatives include methyl esters, ethyl esters, propyl esters, and butyl esters. Two or more of these may be used.
[0107] In polybutylene terephthalate, examples of the aliphatic dicarboxylic acid and the alicyclic dicarboxylic acid include aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, and dimer acid, and alicyclic dicarboxylic acids such as 1,3-cyclohexanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid. Examples of the ester-forming derivatives of aliphatic dicarboxylic acids or alicyclic dicarboxylic acids include lower alkyl esters of the aliphatic dicarboxylic acids and alicyclic dicarboxylic acids. More specifically, examples of the esters include methyl esters, ethyl esters, propyl esters, and butyl esters. Two or more of these may be used.
[0108] In order to efficiently produce polybutylene terephthalate having excellent heat resistance, mechanical properties such as tensile elongation and tensile strength, and chemical resistance, the terephthalic acid and / or its ester-forming derivative (A) is preferably 50 mol % or more, more preferably 90 mol % or more, and most preferably 100 mol % of the total dicarboxylic acid components. It is also preferable to use isophthalic acid and 2,6-naphthalenedicarboxylic acid in combination as aromatic dicarboxylic acid components other than terephthalic acid.
[0109] The diol component constituting the diol residue of polybutylene terephthalate includes 1,4-butanediol, and optionally includes aromatic diols, other aliphatic diols, alicyclic diols, heterocyclic diols, etc. The diol component may be one type or two or more types. These diol components may be derived from either fossil fuels or biomass.
[0110] In polybutylene terephthalate, examples of aromatic diols include bisphenol A derivatives to which ethylene oxide has been added, such as polyoxyethylene-(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene-(2.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene-(2.8)-2,2-bis(4-hydroxyphenyl)propane, and polyoxyethylene-(3.0)-2,2-bis(4-hydroxyphenyl)propane; and bisphenol A derivatives to which propylene oxide has been added, such as polyoxypropylene-(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene-(2.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene-(2.8)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene-(3.0)-2,2-bis(4-hydroxyphenyl)propane. Two or more of these may be used.
[0111] In polybutylene terephthalate, examples of other aliphatic diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, neopentyl glycol, diethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, etc. Two or more of these may be used.
[0112] In polybutylene terephthalate, examples of the alicyclic diol include cyclopentanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol, etc. Two or more of these may be used.
[0113] In polybutylene terephthalate, examples of the heterocyclic diol include isosorbide, isomannide, isoidet, etc. Two or more of these may be used.
[0114] From the viewpoint of efficiently producing polybutylene terephthalate having excellent crystallization characteristics, moldability, heat resistance, and mechanical properties such as tensile elongation and tensile strength, 1,4-butanediol (B) is preferably 50 mol% or more, more preferably 90 mol% or more, and most preferably 100 mol% of all diol components. It is also preferable to use ethylene glycol, 1,3-propanediol, and 1,4-cyclohexanedimethanol in combination as diol components other than 1,4-butanediol.
[0115] From the viewpoint of improving hydrolysis resistance, it is preferable that at least a portion of the terephthalic acid residues and 1,4-butanediol residues of the polybutylene terephthalate are derived from biomass, and it is more preferable that at least a portion of the 1,4-butanediol residues are derived from biomass.
[0116] The thermally adhesive resin layer 4 may contain polybutylene terephthalate at least a part of which is made from a raw material derived from biomass, and further may contain polybutylene terephthalate which is entirely made from a raw material derived from a fossil fuel.
[0117] The heat-sealable resin layer 4 of the present disclosure has a content of biomass-derived carbon based on radioactive carbon (C14) measurement relative to the total carbon, preferably about 1% or more, more preferably about 5% or more, and even more preferably about 10% or more. The upper limit is, for example, about 40%, and preferred ranges include about 1 to 40%, about 5 to 40%, and about 10 to 40%. The results of measuring the plant-derived carbon ratio according to ASTM D-6866 indicate the ratio of carbon from biomass-derived raw materials to the total carbon in the measurement sample. Since carbon dioxide in the atmosphere contains a certain ratio (105.5 pMC) of C14, it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere, such as corn, is also about 105.5 pMC. It is also known that fossil fuels contain almost no C14. Therefore, the ratio of biomass-derived carbon can be calculated by measuring the ratio of C14 contained in the total carbon atoms in the polyester. In the present invention, when the content of C14 in the polyester is defined as PC14, the content of biomass-derived carbon, Pbio, is defined as follows. Pbio(%)=PC14 / 105.5×100
[0118] For example, polyethylene terephthalate is a polymer of ethylene glycol containing 2 carbon atoms and terephthalic acid containing 8 carbon atoms at a molar ratio of 1:1. When only biomass-derived ethylene glycol is used, the content of biomass-derived carbon in the polyester, Pbio, is 20%. In the present invention, the content of biomass-derived carbon determined by radiocarbon (C14) measurement is preferably 10 to 19% relative to the total carbon in the resin composition. If the biomass-derived carbon content in the resin composition is less than 10%, the effect as a carbon offset material is poor. On the other hand, as described above, the biomass-derived carbon content in the resin composition is preferably as close to 20% as possible, but due to problems in the manufacturing process of the polyester film and in terms of physical properties, it is preferable that the resin contains recycled polyester and additives as described above, so the actual upper limit is 18%.
[0119] The heat-fusible resin layer 4 containing polyester A may be, for example, a resin film formed from a resin, or may be formed by applying a resin. The resin film may be an unstretched film or a stretched film. The resin film is preferably an unstretched film. Examples of stretched films include uniaxially stretched films and biaxially stretched films, and biaxially stretched films are preferred. Examples of stretching methods for forming biaxially stretched films include sequential biaxial stretching, inflation, and simultaneous biaxial stretching. Examples of methods for applying a resin include roll coating, gravure coating, and extrusion coating.
[0120] The heat-sealable resin layer 4 containing polyester A preferably has the following tensile properties (tensile breaking strength (MPa), tensile breaking elongation (%), and stress at 5% elongation (MPa) for each MD and TD test piece (width 15 mm, length 150 mm, MD test piece length direction is MD, TD test piece length is TD)).
[0121] The tensile breaking strength A1 (MPa) of a test piece in the MD of the heat-fusible resin layer 4 containing polyester A is preferably about 210 MPa or more, more preferably about 220 MPa or more, and even more preferably about 230 MPa or more, and is preferably about 270 MPa or less, more preferably about 260 MPa or less, and even more preferably about 250 MPa or less, and preferred ranges include about 210 to 270 MPa, about 210 to 260 MPa, about 210 to 250 MPa, about 220 to 270 MPa, about 220 to 260 MPa, about 220 to 250 MPa, about 230 to 270 MPa, about 230 to 260 MPa, and about 230 to 250 MPa.
[0122] The tensile breaking strength A2 (MPa) of a test piece TD of the heat-fusible resin layer 4 containing polyester A is preferably about 230 MPa or more, more preferably about 240 MPa or more, and even more preferably about 250 MPa or more, and is preferably about 300 MPa or less, more preferably about 290 MPa or less, and even more preferably about 280 MPa or less, and preferred ranges include about 230 to 300 MPa, about 230 to 290 MPa, about 230 to 280 MPa, about 240 to 300 MPa, about 240 to 290 MPa, about 240 to 280 MPa, about 250 to 300 MPa, about 250 to 290 MPa, and about 250 to 280 MPa.
[0123] The tensile elongation at break (%) of a test piece in the MD of the heat-fusible resin layer 4 containing polyester A is preferably about 80% or more, more preferably about 90% or more, and even more preferably about 100% or more, and is preferably about 150% or less, more preferably about 140% or less, and even more preferably about 130% or less, and preferred ranges include about 80 to 150%, about 80 to 140%, about 80 to 130%, about 90 to 150%, about 90 to 140%, about 90 to 130%, about 100 to 150%, about 100 to 140%, and about 100 to 130%.
[0124] The tensile elongation at break (%) of a TD test piece of the heat-fusible resin layer 4 containing polyester A is preferably about 70% or more, more preferably about 80% or more, and even more preferably about 90% or more, and is preferably about 130% or less, more preferably about 120% or less, and even more preferably about 110% or less, and preferred ranges include about 70 to 130%, about 70 to 120%, about 70 to 110%, about 80 to 130%, about 80 to 120%, about 80 to 110%, about 90 to 130%, about 90 to 120%, and about 90 to 110%.
[0125] The stress B1 (MPa) at 5% elongation of a test piece in the MD of the heat-fusible resin layer 4 containing polyester A is preferably about 90 MPa or more, more preferably about 100 MPa or more, and even more preferably about 105 MPa or more, and is preferably about 130 MPa or less, more preferably about 120 MPa or less, and even more preferably about 110 MPa or less, and preferred ranges include about 90 to 130 MPa, about 90 to 120 MPa, about 90 to 110 MPa, about 100 to 130 MPa, about 100 to 120 MPa, about 100 to 110 MPa, about 105 to 130 MPa, about 105 to 120 MPa, and about 105 to 110 MPa.
[0126] Stress B at 5% elongation of a test piece of TD of the heat-sealable resin layer 4 containing polyester A 2 (MPa) is preferably about 90 MPa or more, more preferably about 95 MPa or more, and even more preferably about 100 MPa or more, and is preferably about 115 MPa or less, more preferably about 110 MPa or less, and even more preferably about 100 MPa or less, and preferred ranges include about 90 to 115 MPa, about 90 to 110 MPa, about 90 to 100 MPa, about 95 to 115 MPa, about 95 to 110 MPa, about 95 to 100 MPa, about 100 to 115 MPa, and about 100 to 110 MPa.
[0127] In addition, the tensile breaking strength A of the test piece of polyester A in the MD of the heat-sealable resin layer 4 at 5% elongation with respect to the stress B1 (MPa) 1 (MPa) ratio (A 1 / B 1 ) is preferably about 1.5 or more, more preferably about 2.0 or more, and even more preferably about 2.5 or more, and is preferably about 3.5 or less, more preferably about 3.0 or less, and even more preferably about 2.5 or less. Preferred ranges include about 1.5 to 3.5, about 1.5 to 3.0, about 1.5 to 2.5, about 2.0 to 3.5, about 2.0 to 3.0, about 2.0 to 2.5, about 2.5 to 3.5, and about 2.5 to 3.0.
[0128] The ratio (A2 / B2) of the tensile breaking strength A2 (MPa) to the stress B2 (MPa) at 5% elongation of a TD test piece of the heat-fusible resin layer 4 containing polyester A is preferably about 1.5 or more, more preferably about 2.0 or more, and even more preferably about 2.5 or more, and is preferably about 4.0 or less, more preferably about 3.5 or less, and even more preferably about 3.0 or less, and preferred ranges include about 1.5 to 4.0, about 1.5 to 3.5, about 1.5 to 3.0, about 2.0 to 4.0, about 2.0 to 3.5, about 2.0 to 3.0, about 2.5 to 4.0, about 2.5 to 3.5, and about 2.5 to 3.0.
[0129] <Method of measuring tensile properties> The heat-sealable resin layer 4 containing polyester A is cut into test pieces of width 15 mm and length 150 mm from each of MD and TD (the test pieces in MD have a length in the MD direction, and the test pieces in TD have a length in the TD direction), and the strength and elongation of the test pieces are measured using a tensile tester (for example, an automatic film strength and elongation measuring device "Tensilon AMF / RTA-100" manufactured by Orientec Co., Ltd.). In addition, the F5 values (tensile strength when the film is stretched by 5%) in MD and TD are measured.
[0130] In addition, for a MD test piece of the heat-sealable resin layer 4 containing polyester A (width 15 mm, length 150 mm, the length direction of the MD test piece is MD), in accordance with JIS C-2318:2020, the heat shrinkage rate when placed in an air, 150 ° C. environment for 30 minutes is preferably about 1.0% or more, more preferably about 1.5% or more, and even more preferably about 2.0% or more, and is also preferably about 3.5% or less, more preferably about 3.0% or less, and even more preferably about 2.5% or less, and preferred ranges are about 1.0 to 3.5%, about 1.0 to 3.0%, about 1.0 to 2.5%, about 1.5 to 3.5%, about 1.5 to 3.0%, about 1.5 to 2.5%, about 2.0 to 3.5%, about 2.0 to 3.0%, and about 2.0 to 2.5%.
[0131] In addition, for a TD test piece of the heat-sealable resin layer 4 containing polyester A (width 15 mm, length 150 mm, the length direction of the TD test piece is TD), in accordance with JIS C-2318:2020, the heat shrinkage rate when placed in an air, 150 ° C. environment for 30 minutes is preferably about 0.1% or more, more preferably about 0.3% or more, and even more preferably about 0.5% or more, and is also preferably about 1.5% or less, more preferably about 1.0% or less, and even more preferably about 0.5% or less, and preferred ranges include about 0.1 to 1.5%, about 0.1 to 1.0%, about 0.1 to 0.5%, about 0.3 to 1.5%, about 0.3 to 1.0%, about 0.3 to 0.5%, about 0.5 to 1.5%, and about 0.5 to 1.0%.
[0132] <Method of measuring heat shrinkage rate> For the heat-fusible resin layer 4 containing polyester A, test pieces (width 15 mm, length 150 mm, the length direction of the MD test piece is the MD, and the length direction of the TD test piece is the TD) cut out from each of the MD and TD are placed in a heating oven at 150°C and heat-treated at 150°C for 30 minutes in accordance with JIS C-2318:2020, and the thermal shrinkage rate is measured.
[0133] Furthermore, the heat-fusible resin layer 4 may further contain other resins different from polyester, as long as the heat-fusible resin layer 4 exhibits heat-fusible properties.
[0134] As the other resin, a resin containing a polyolefin skeleton, such as polyolefin or acid-modified polyolefin, is preferable. The fact that the resin constituting the heat-fusible resin layer 4 contains a polyolefin skeleton can be analyzed, for example, by infrared spectroscopy, gas chromatography mass spectrometry, or the like. Furthermore, when the resin constituting the heat-fusible resin layer 4 is analyzed by infrared spectroscopy, it is preferable that a peak derived from maleic anhydride is detected. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, a peak derived from maleic anhydride at a wave number of 1760 cm is detected. -1 Nearby and wave number 1780cm -1A peak derived from maleic anhydride is detected around 1000 nm. When the thermally adhesive resin layer 4 contains a maleic anhydride-modified polyolefin, a peak derived from maleic anhydride is detected by infrared spectroscopy. However, if the degree of acid modification is low, the peak becomes small and may not be detected. In that case, analysis can be performed by nuclear magnetic resonance spectroscopy.
[0135] Specific examples of polyolefins include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; and ethylene-butene-propylene terpolymers. Among these, polypropylene is preferred. When the polyolefin resin is a copolymer, it may be a block copolymer or a random copolymer. These polyolefin resins may be used alone or in combination of two or more.
[0136] The polyolefin may be a cyclic polyolefin. The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, styrene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; and cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Among these, cyclic alkenes are preferred, and norbornene is more preferred.
[0137] The polyolefin may be an acid-modified polyolefin. The acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of a polyolefin with an acid component. The polyolefin to be acid-modified may be the above-mentioned polyolefin, a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. The acid component used for the acid modification may be, for example, a carboxylic acid or an anhydride such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, or itaconic anhydride.
[0138] The acid-modified polyolefin may be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin by replacing it with an acid component, or by block-polymerizing or graft-polymerizing an acid component to the cyclic polyolefin. The cyclic polyolefin to be acid-modified is the same as described above. The acid component used for the acid modification is the same as the acid component used for the modification of the polyolefin.
[0139] Preferred acid-modified polyolefins include polyolefins modified with a carboxylic acid or anhydride thereof, polypropylenes modified with a carboxylic acid or anhydride thereof, maleic anhydride-modified polyolefins, and maleic anhydride-modified polypropylenes.
[0140] The heat-sealable resin layer 4 may be formed of one type of resin alone, or may be formed of a blend polymer of two or more types of resins. The heat-sealable resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resins. For example, at least one layer of the heat-sealable resin layer 4 may be a layer containing polybutylene terephthalate formed from the above-mentioned biomass-derived raw material, and the other layers of the heat-sealable resin layer 4 may be layers not containing the polybutylene terephthalate.
[0141] When the thermally adhesive resin layer 4 is laminated with the barrier layer 3, the adhesive layer 5, or the like to produce the exterior packaging material 10 for an electricity storage device of the present disclosure, a preformed resin film may be used as the thermally adhesive resin layer 4. In addition, the thermally adhesive resin that forms the thermally adhesive resin layer 4 may be formed into a film on the surface of the barrier layer 3, the adhesive layer 5, or the like by extrusion molding, coating, or the like, to form the thermally adhesive resin layer 4 from a resin film.
[0142] The thermally adhesive resin layer 4 may contain a lubricant, etc., if necessary. When the thermally adhesive resin layer 4 contains a lubricant, the moldability of the exterior material for a power storage device can be improved. The lubricant is not particularly limited, and any known lubricant can be used.
[0143] The lubricant is not particularly limited, but preferably includes an amide-based lubricant. Specific examples of the lubricant include those exemplified for the base layer 1. The lubricant may be used alone or in combination of two or more types, and is preferably used in combination of two or more types.
[0144] In the present disclosure, from the viewpoint of improving the moldability of the exterior material for a power storage device, it is preferable that a lubricant is present on at least one of the surface and the inside of the heat-sealable resin layer 4. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, and N,N'-distearylisophthalic acid amide.The lubricant may be used alone or in combination of two or more kinds, and it is preferable to use a combination of two or more kinds.
[0145] When a lubricant is present on the surface of the heat-sealable resin layer 4, the amount of the lubricant is not particularly limited. However, from the viewpoint of improving the formability of the exterior material for an electrical storage device, the amount of the lubricant is preferably about 1 mg / m 2 More preferably, about 3 mg / m 2 More preferably, about 5 mg / m 2 More preferably, about 10 mg / m 2 More preferably, about 15 mg / m 2 or more, and preferably about 50 mg / m 2 or less, more preferably about 40 mg / m 2 The preferred range is 1 to 50 mg / m 2 degree, 1~40mg / m 2 degree, 3~50mg / m 2 degree, 3~40mg / m 2 degree, 5~50mg / m 2 degree, 5~40mg / m 2 degree, 10~50mg / m 2 degree, 10~40mg / m 2 degree, 15~50mg / m 2 degree, 15~40mg / m 2 The degree of
[0146] When a lubricant is present inside the heat-sealable resin layer 4, the amount of the lubricant is not particularly limited, but from the viewpoint of improving the moldability of the exterior material for an electrical storage device, it is preferably about 100 ppm or more, more preferably about 300 ppm or more, and even more preferably about 500 ppm or more, and is preferably about 3000 ppm or less, more preferably about 2000 ppm or less, and preferred ranges include about 100 to 3000 ppm, about 100 to 2000 ppm, about 300 to 3000 ppm, about 300 to 2000 ppm, about 500 to 3000 ppm, and about 500 to 2000 ppm. When two or more types of lubricants are present inside the heat-sealable resin layer 4, the above amount of lubricant is the total amount of lubricant. Furthermore, when two or more types of lubricants are present inside the heat-sealable resin layer 4, the amount of the first type of lubricant is not particularly limited, but from the viewpoint of improving the formability of the exterior material for an electricity storage device, it is preferably about 100 ppm or more, more preferably about 300 ppm or more, even more preferably about 500 ppm or more, and is preferably about 3000 ppm or less, more preferably about 2000 ppm or less, and preferred ranges include about 100 to 3000 ppm, about 100 to 2000 ppm, about 300 to 3000 ppm, about 300 to 2000 ppm, about 500 to 3000 ppm, and about 500 to 2000 ppm. The amount of the second type of lubricant is not particularly limited, but from the viewpoint of improving the formability of the exterior material for an electricity storage device, it is preferably about 50 ppm or more, more preferably about 100 ppm or more, and even more preferably about 200 ppm or more, and is preferably about 1500 ppm or less, more preferably about 1000 ppm or less, and preferred ranges include about 50 to 1500 ppm, about 50 to 1000 ppm, about 100 to 1500 ppm, about 100 to 1000 ppm, about 200 to 1500 ppm, and about 200 to 1000 ppm.
[0147] The lubricant present on the surface of the heat-fusible resin layer 4 may be a lubricant exuded from the resin constituting the heat-fusible resin layer 4, or a lubricant applied to the surface of the heat-fusible resin layer 4.
[0148] The thickness of the heat-sealable resin layer 4 is not particularly limited as long as the heat-sealable resin layers are heat-sealed to each other to seal the electricity storage device element, and may be, for example, about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. For example, when the thickness of the adhesive layer 5 described below is 10 μm or more, the thickness of the heat-sealable resin layer 4 is preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 5 described below is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-sealable resin layer 4 is preferably about 20 μm or more, and more preferably about 35 to 85 μm.
[0149] [Adhesive layer 5] In the packaging material for an electricity storage device of the present disclosure, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 (or the corrosion-resistant film) and the heat-sealable resin layer 4 in order to firmly bond them together.
[0150] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-fusible resin layer 4. As the resin used to form the adhesive layer 5, for example, the same adhesive as exemplified for the adhesive layer 2 can be used.
[0151] When the resin used to form the adhesive layer 5 contains a polyolefin skeleton, the adhesive layer 5 preferably contains a resin containing a polyolefin skeleton as a main component, more preferably contains an acid-modified polyolefin as a main component, and even more preferably contains an acid-modified polypropylene as a main component. Here, the main component means that the content of the resin component contained in the adhesive layer 5 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more. For example, the adhesive layer 5 contains acid-modified polypropylene as a main component means that the content of the acid-modified polypropylene among the resin components contained in the adhesive layer 5 is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.
[0152] The resin constituting the adhesive layer 5 can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, etc., and the analysis method is not particularly limited, to determine whether the resin constituting the adhesive layer 5 contains a polyolefin skeleton. In addition, the resin constituting the adhesive layer 5 can be analyzed by, for example, infrared spectroscopy to determine whether the maleic anhydride-modified polyolefin contains an acid-modified polyolefin at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0153] Furthermore, from the viewpoint of ensuring durability such as heat resistance and resistance to contents of the exterior material for an electricity storage device, and moldability while reducing the thickness, the adhesive layer 5 is more preferably a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include those mentioned above.
[0154] The adhesive layer 5 is preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition containing an acid-modified polyolefin and at least one selected from the group consisting of a compound having an isocyanate group and a compound having an epoxy group. The adhesive layer 5 is preferably at least one selected from the group consisting of polyurethane, polyester, and epoxy resin, and more preferably contains polyurethane and epoxy resin. As the polyester, for example, an ester resin generated by the reaction of an epoxy group with a maleic anhydride group, and an amide ester resin generated by the reaction of an oxazoline group with a maleic anhydride group are preferable. In addition, when unreacted substances of a curing agent such as a compound having an isocyanate group, a compound having an oxazoline group, or an epoxy resin remain in the adhesive layer 5, the presence of the unreacted substances can be confirmed by a method selected from, for example, infrared spectroscopy, Raman spectroscopy, time-of-flight secondary ion mass spectrometry (TOF-SIMS), etc.
[0155] In addition, from the viewpoint of further increasing the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent having at least one selected from the group consisting of an oxygen atom, a heterocycle, a C=N bond, and a COC bond. Examples of the curing agent having a heterocycle include a curing agent having an oxazoline group and a curing agent having an epoxy group. Examples of the curing agent having a C=N bond include a curing agent having an oxazoline group and a curing agent having an isocyanate group. Examples of the curing agent having a COC bond include a curing agent having an oxazoline group and a curing agent having an epoxy group. The fact that the adhesive layer 5 is a cured product of a resin composition containing these curing agents can be confirmed by, for example, gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), X-ray photoelectron spectroscopy (XPS), or other methods.
[0156] The compound having an isocyanate group is not particularly limited, but from the viewpoint of effectively increasing the adhesion between the barrier layer 3 and the adhesive layer 5, a polyfunctional isocyanate compound is preferably used. The polyfunctional isocyanate compound is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate-based curing agents include pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers. In addition, adducts, biurets, isocyanurates, etc. are also included.
[0157] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0158] The compound having an oxazoline group is not particularly limited as long as it is a compound having an oxazoline skeleton. Specific examples of the compound having an oxazoline group include those having a polystyrene main chain and those having an acrylic main chain. In addition, examples of commercially available products include the Epocross series manufactured by Nippon Shokubai Co., Ltd.
[0159] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0160] An example of a compound having an epoxy group is an epoxy resin. The epoxy resin is not particularly limited as long as it is a resin capable of forming a crosslinked structure by the epoxy group present in the molecule, and a known epoxy resin can be used. The weight average molecular weight of the epoxy resin is preferably about 50 to 2000, more preferably about 100 to 1000, and even more preferably about 200 to 800. In the present disclosure, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under conditions using polystyrene as a standard sample.
[0161] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, bisphenol F glycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, polyglycerin polyglycidyl ether, etc. The epoxy resins may be used alone or in combination of two or more.
[0162] The ratio of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0163] The polyurethane is not particularly limited, and any known polyurethane can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing polyurethane.
[0164] The proportion of polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, and more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This makes it possible to effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5 in an atmosphere containing a component that induces corrosion of the barrier layer, such as an electrolyte solution.
[0165] In addition, when the adhesive layer 5 is a cured product of a resin composition containing at least one selected from the group consisting of a compound having an isocyanate group, a compound having an oxazoline group, and an epoxy resin, and the acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group, and the compound having an epoxy group each function as a curing agent.
[0166] The adhesive layer 5 may contain a modifier having a carbodiimide group.
[0167] When the adhesive layer 5 is laminated with the barrier layer 3, the heat-sealable resin layer 4, or the like to produce the exterior packaging material 10 for an electricity storage device of the present disclosure, a preformed resin film may be used as the adhesive layer 5. The heat-sealable resin that forms the adhesive layer 5 may be formed into a film on the surface of the barrier layer 3, the heat-sealable resin layer 4, or the like by extrusion molding, coating, or the like, to form the adhesive layer 5 from a resin film.
[0168] The thickness of the adhesive layer 5 is preferably about 50 μm or less, about 40 μm or less, about 30 μm or less, about 20 μm or less, or about 5 μm or less. The thickness of the adhesive layer 5 is preferably about 0.1 μm or more, or about 0.5 μm or more. The thickness of the adhesive layer 5 is preferably in the range of about 0.1 to 50 μm, about 0.1 to 40 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 40 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, or about 0.5 to 5 μm. More specifically, in the case of the adhesive exemplified in the adhesive layer 2 or a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 1 to 10 μm, more preferably about 1 to 5 μm. When a resin exemplified for the heat-fusible resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When the adhesive layer 5 is an adhesive exemplified for the adhesive layer 2 or a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed, for example, by applying the resin composition and curing it by heating or the like. When a resin exemplified for the heat-fusible resin layer 4 is used, the adhesive layer 5 can be formed, for example, by extrusion molding the heat-fusible resin layer 4 and the adhesive layer 5.
[0169] [Surface coating layer 6] The exterior material for an electricity storage device according to the present disclosure may have a surface coating layer 6 on the substrate layer 1 (the side of the substrate layer 1 opposite to the barrier layer 3) as necessary, for the purpose of improving at least one of design, electrolyte resistance, scratch resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer side of the exterior material for an electricity storage device when an electricity storage device is assembled using the exterior material for an electricity storage device.
[0170] The surface coating layer 6 may be made of, for example, a resin such as polyvinylidene chloride, polyester, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, or phenol resin, or a modified product of these resins. It may also be a copolymer of these resins or a modified product of the copolymer. Furthermore, it may be a mixture of these resins. The resin is preferably a curable resin. That is, the surface coating layer 6 is preferably made of a cured product of a resin composition containing a curable resin.
[0171] When the resin forming the surface coating layer 6 is a curable resin, the resin may be either a one-component curable type or a two-component curable type, but is preferably a two-component curable type. Examples of two-component curable resins include two-component curable polyurethane, two-component curable polyester, and two-component curable epoxy resin. Among these, two-component curable polyurethane is preferred.
[0172] Examples of two-component curing polyurethane include polyurethanes containing a first agent containing a polyol compound and a second agent containing an isocyanate compound. Preferably, two-component curing polyurethanes are made of a polyol such as polyester polyol, polyether polyol, and acrylic polyol as the first agent, and an aromatic or aliphatic polyisocyanate as the second agent. Examples of polyurethanes include polyurethane compounds in which a polyol compound and an isocyanate compound have been reacted in advance, and polyurethanes containing an isocyanate compound. Examples of polyurethanes include polyurethane compounds in which a polyol compound and an isocyanate compound have been reacted in advance, and polyurethanes containing a polyol compound. Examples of polyurethanes include polyurethanes in which a polyurethane compound in which a polyol compound and an isocyanate compound have been reacted in advance is cured by reacting it with moisture in the air or the like. As the polyol compound, it is preferable to use a polyester polyol having a hydroxyl group on the side chain in addition to the hydroxyl group at the end of the repeating unit. As the second agent, aliphatic, alicyclic, aromatic, and araliphatic isocyanate compounds are included. Examples of isocyanate compounds include hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI), isophorone diisocyanate (IPDI), hydrogenated XDI (H6XDI), hydrogenated MDI (H12MDI), tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and naphthalene diisocyanate (NDI). In addition, examples of the isocyanate compounds include polyfunctional isocyanate modified compounds made from one or more of these diisocyanates. In addition, a polymer (e.g., a trimer) can also be used as the polyisocyanate compound. Examples of such polymers include adducts, biurets, and nurates. In addition, an aliphatic isocyanate compound refers to an isocyanate having an aliphatic group and no aromatic ring, an alicyclic isocyanate compound refers to an isocyanate having an alicyclic hydrocarbon group, and an aromatic isocyanate compound refers to an isocyanate having an aromatic ring.Since the surface coating layer 6 is formed from polyurethane, excellent electrolyte resistance is imparted to the exterior material for an electricity storage device.
[0173] The surface coating layer 6 may contain additives such as the above-mentioned lubricant, antiblocking agent, matting agent, flame retardant, antioxidant, tackifier, and antistatic agent in at least one of the surface and the inside of the surface coating layer 6, as necessary, depending on the functionality to be provided to the surface of the surface coating layer 6. Examples of the additives include fine particles having an average particle size of about 0.5 nm to 5 μm. The average particle size of the additive is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.
[0174] The additive may be either inorganic or organic. The shape of the additive is not particularly limited, and examples of the shape include spherical, fibrous, plate-like, amorphous, and scaly.
[0175] Specific examples of additives include talc, silica, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, alumina, carbon black, carbon nanotubes, high melting point nylon, acrylate resin, crosslinked acrylic, crosslinked styrene, crosslinked polyethylene, benzoguanamine, gold, aluminum, copper, nickel, etc. The additives may be used alone or in combination of two or more. Among these additives, silica, barium sulfate, and titanium oxide are preferable from the viewpoint of dispersion stability and cost. In addition, the additives may be subjected to various surface treatments such as insulation treatment and high dispersibility treatment.
[0176] The method for forming the surface coating layer 6 is not particularly limited, and examples thereof include a method for applying a resin that forms the surface coating layer 6. When an additive is blended into the surface coating layer 6, a resin mixed with the additive may be applied.
[0177] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.
[0178] 3. Manufacturing method for exterior material for power storage device The manufacturing method of the exterior material for an electricity storage device is not particularly limited, so long as a laminate is obtained in which the layers of the exterior material for an electricity storage device of the present invention are stacked together, and the method includes a step of obtaining a laminate in which, from the outside, at least a base material layer, a barrier layer, and a heat-sealable resin layer are stacked together, the heat-sealable resin layer containing polyester, and at least a portion of the polyester is formed from a raw material derived from biomass.
[0179] An example of a method for producing an exterior material for an electricity storage device according to the present disclosure is as follows. First, a laminate (hereinafter, sometimes referred to as "laminate A") is formed in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in this order. Specifically, the laminate A can be formed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied to the base layer 1 or to the barrier layer 3, the surface of which has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then dried, and the barrier layer 3 or base layer 1 is laminated thereon, and the adhesive layer 2 is cured.
[0180] Next, the heat-sealable resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-sealable resin layer 4 is directly laminated on the barrier layer 3, the heat-sealable resin layer 4 may be laminated on the barrier layer 3 of the laminate A by a method such as a thermal lamination method or an extrusion lamination method. When an adhesive layer 5 is provided between the barrier layer 3 and the heat-sealable resin layer 4, the adhesive layer 5 and the heat-sealable resin layer 4 may be laminated, for example, by (1) an extrusion lamination method, (2) a thermal lamination method, (3) a sandwich lamination method, or (4) a dry lamination method. Examples of the (1) extrusion lamination method include a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 by extruding them onto the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method), and the like. Examples of the (2) thermal lamination method include a method of forming a laminate in which an adhesive layer 5 and a heat-sealable resin layer 4 are laminated separately, and laminating the laminate on the barrier layer 3 of the laminate A, or a method of forming a laminate in which an adhesive layer 5 is laminated on the barrier layer 3 of the laminate A, and laminating the laminate on the heat-sealable resin layer 4. Examples of the (3) sandwich lamination method include a method of laminating the laminate A and the heat-sealable resin layer 4 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-sealable resin layer 4 previously formed into a sheet. Examples of the (4) dry lamination method include a method of coating the barrier layer 3 of the laminate A with an adhesive for forming the adhesive layer 5 as a solution, drying the adhesive, or baking the adhesive, and laminating the heat-sealable resin layer 4 previously formed into a sheet on the adhesive layer 5.
[0181] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer 6 on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer 6 on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer 6.
[0182] As described above, a laminate is formed which includes, in this order, the optional surface coating layer 6 / the base material layer 1 / the optional adhesive layer 2 / the barrier layer 3 / the optional adhesive layer 5 / the heat-sealable resin layer 4. In order to strengthen the adhesion of the optional adhesive layer 2 and the optional adhesive layer 5, the laminate may be subjected to a heat treatment.
[0183] In the exterior packaging material for an electricity storage device, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, to improve the processability. For example, by subjecting the surface of the base layer 1 opposite to the barrier layer 3 to corona treatment, the printability of the ink on the surface of the base layer 1 can be improved.
[0184] 4. Applications of exterior materials for energy storage devices The exterior material for an electricity storage device according to the present disclosure is used in a package for hermetically housing an electricity storage device element such as a positive electrode, a negative electrode, an electrolyte, etc. That is, an electricity storage device can be formed by housing an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte in a package formed from the exterior material for an electricity storage device according to the present disclosure.
[0185] Specifically, an electricity storage device element having at least a positive electrode, a negative electrode, and an electrolyte is covered with the exterior material for an electricity storage device of the present disclosure in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the electricity storage device element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide an electricity storage device using the exterior material for an electricity storage device. When an electricity storage device element is housed in a package formed with the exterior material for an electricity storage device of the present disclosure, the package is formed so that the heat-sealable resin portion of the exterior material for an electricity storage device of the present disclosure faces inside (the surface in contact with the electricity storage device element). The heat-sealable resin layers of two electric storage device exterior materials may be stacked facing each other, and the peripheral parts of the stacked electric storage device exterior materials may be heat-sealed to form a package. Alternatively, as shown in the example of FIG. 5, one electric storage device exterior material may be folded back and stacked, and the peripheral parts may be heat-sealed to form a package. When folding back and stacking, as shown in the example of FIG. 5, the sides other than the folded side may be heat-sealed to form a package by sealing on three sides, or the material may be folded back to form a flange and sealed on all four sides. Alternatively, the electric storage device exterior material may be wrapped around the electric storage device element, the heat-sealable resin layers may be sealed to form a heat-sealed part, and a lid or the like may be arranged to close the openings at both ends, and the lid may be heat-sealed to the electric storage device exterior material wrapped around the electric storage device element. The lid may be formed, for example, from a resin molded product, a metal molded product, an electric storage device exterior material, or the like. In addition, a recess for accommodating an electricity storage device element may be formed in the exterior material for an electricity storage device by deep drawing or stretch molding. As in the example shown in Fig. 5, a recess may be provided in one exterior material for an electricity storage device and no recess may be provided in the other exterior material for an electricity storage device, or a recess may be provided in the other exterior material for an electricity storage device.
[0186] The exterior material for an electric storage device of the present disclosure can be suitably used for an electric storage device such as a battery (including a condenser, a capacitor, etc.). The exterior material for an electric storage device of the present disclosure may be used for either a primary battery or a secondary battery, but is preferably used for a secondary battery. The type of secondary battery to which the exterior material for an electric storage device of the present disclosure is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, all-solid batteries, semi-solid batteries, quasi-solid batteries, polymer batteries, all-resin batteries, lead-acid batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, capacitors, etc. Among these secondary batteries, examples of suitable applications of the exterior material for an electric storage device of the present disclosure include lithium ion batteries and lithium ion polymer batteries. EXAMPLES
[0187] The present disclosure will be described in detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the examples.
[0188] <Synthesis of PBT containing biomass-derived raw materials> A 1,4-butanediol fermentation broth was obtained by microbial fermentation (see WO 2008 / 115840). The fermentation broth was purified to obtain 1,4-butanediol by direct fermentation (see WO 2010 / 141780).
[0189] Next, 100 g of the obtained 1,4-butanediol was heated to 100°C, and 11.2 g of a titanium compound: tetra-n-butoxy titanate (TBT) (manufactured by Tokyo Chemical Industry Co., Ltd.) was mixed to obtain a catalyst solution. Terephthalic acid (TPA) (manufactured by Tokyo Chemical Industry Co., Ltd.) as a dicarboxylic acid component, 1,4-butanediol (B), and 4.6 mL of the catalyst solution obtained by the above method as an esterification (ES) reaction catalyst were charged into a reactor equipped with a rectification column. At this time, the molar ratio ((B) / (A-1)) of 1,4-butanediol (B) to TPA (A-1) was 1.8, and the amount of TBT added to 100 g of polybutylene terephthalate produced was 1.3 x 10-4 The amount of TBT added to the reaction mixture was 0.5×10 mol per 100 g of polybutylene terephthalate. -2 0.49 mL of the catalyst solution obtained by the above method was added so that the total weight of the catalyst was 0.05 parts by weight per 100 parts by weight of polybutylene terephthalate, and a polycondensation reaction was carried out for 230 minutes under conditions of a temperature of 245°C and a pressure of 100 Pa, obtaining pellets of polybutylene terephthalate containing biomass-derived raw materials (30% biomass-derived carbon).
[0190] <Preparation of PBT film derived from biomass> 90 parts by mass of the PBT pellets containing biomass-derived raw materials obtained as described above and 10 parts by mass of a fossil fuel-derived polyethylene terephthalate master batch were dried and then fed into an extruder, melted at 285°C, extruded into a sheet from a T-die, and cooled and solidified with a cooling roll to obtain an unstretched PBT film with a thickness of 20 μm (the proportion of biomass-derived carbon was 27%).
[0191] <Preparation of PBT film derived from fossil fuels> Polybutylene terephthalate (intrinsic viscosity 0.85 dl / g) produced from conventional raw materials derived from fossil fuels was fed into an extruder, melted at 285°C, extruded into a sheet from a T-die, and cooled and solidified on a cooling roll to obtain an unstretched PBT film (derived from fossil fuels (0% biomass-derived carbon)).
[0192] <Manufacture of exterior materials for power storage devices> Example 1 A laminated film was prepared as the substrate layer, in which a biaxially oriented PET film (thickness 12 μm) and an oriented nylon film (thickness 15 μm) were bonded with a two-liquid urethane adhesive (polyol compound and aromatic isocyanate compound, thickness after curing is 3 μm). In addition, an aluminum foil (JIS H4160:1994 A8021H-O (thickness 40 μm)) was prepared as the barrier layer. Using a two-liquid urethane adhesive (polyol compound and aromatic isocyanate compound), the stretched nylon film side of the aluminum foil and the substrate layer were laminated by dry lamination so that the thickness of the adhesive layer after curing was 3 μm, and then aging treatment was performed to produce a substrate layer / adhesive layer / barrier layer laminate. Both sides of the aluminum foil were subjected to chemical conversion treatment. The chemical conversion treatment of the aluminum foil was performed using a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid, with a coating amount of chromium of 10 mg / m 2 (dry weight) was applied to both sides of an aluminum foil by roll coating, and then baked.
[0193] Next, the barrier layer side of the laminate obtained above and the unstretched PBT film (20 μm thick, 27% biomass-derived carbon content) serving as a heat-sealable resin layer were laminated by dry lamination using a two-component urethane adhesive (polyol compound and aromatic isocyanate compound) so that the adhesive layer had a thickness of 3 μm after curing. The aluminum foil and the heat-sealable resin layer were then laminated together by a dry lamination method, and an aging treatment was then performed to laminate the adhesive layer / heat-sealable resin layer on top of the barrier layer, thereby obtaining an exterior material for an electricity storage device in which the substrate layer / adhesive layer / barrier layer / adhesive layer / heat-sealable resin layer were laminated in that order.
[0194] Comparative Example 1 Except for using the unstretched PBT film (derived from fossil fuels (0% of carbon derived from biomass), thickness 20 μm) as the heat-sealable resin layer, an exterior material for an electricity storage device was obtained in the same manner as in Example 1, in which a base layer / adhesive layer / barrier layer / adhesive layer / heat-sealable resin layer were laminated in that order.
[0195] <Measurement of limit forming depth> Each exterior material for an electricity storage device was cut into a rectangle with a length (MD direction) of 80 mm and a width (TD direction) of 120 mm to prepare a test sample. The MD of the exterior material for an electricity storage device corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the exterior material for an electricity storage device corresponds to the TD of the aluminum alloy foil. This sample was placed in a 25°C environment in a rectangular mold (female mold, the surface has a maximum height roughness (nominal value of Rz) of 3.2μm as specified in Table 2 of the surface roughness standard for comparison in JIS B 0659-1:2002, Annex 1 (Reference), corner R2.0mm, ridge R1.0mm) with an aperture of 30mm (MD) x 60mm (TD) and a corresponding mold (male mold, the surface of the ridgeline has a maximum height roughness (nominal value of Rz) of 1.6μm as specified in Table 2 of the surface roughness standard for comparison in JIS B 0659-1:2002, Annex 1 (Reference), corner R2.0mm, ridge R1.0mm). The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard piece is 3.2 μm. Using a corner R2.0 mm, ridge R1.0 mm), the molding depth was changed in 0.5 mm increments from a molding depth of 0.5 mm at a pressing pressure (surface pressure) of 0.25 MPa, and cold molding (one-stage drawing molding) was performed on 10 samples each. At this time, the above test sample was placed on a female mold so that the heat-fusible resin layer side was located on the male mold side and molding was performed. In addition, the clearance between the male mold and the female mold was 0.3 mm. The sample after cold molding was irradiated with light from a penlight in a dark room to confirm whether pinholes or cracks were generated in the aluminum foil due to the transmission of light. The deepest molding depth at which no pinholes or cracks occurred in the aluminum foil in any of the 10 samples was defined as A mm, and the number of samples at which pinholes or other defects occurred in the aluminum foil at the shallowest molding depth was defined as B. The value calculated using the following formula was rounded off to two decimal places to determine the limit molding depth of the exterior material for electricity storage devices. Limit forming depth = A mm + (0.5 mm / 10 pieces) x (10 pieces - B pieces)
[0196] The limit forming depth of the exterior material for an electricity storage device of Example 1 was 8.6 mm, and the limit forming depth of the exterior material for an electricity storage device of Comparative Example 1 was 8.5 mm, which were the same limit forming depth.
[0197] As described above, the present disclosure provides the following aspects of the invention. Item 1. The device is composed of a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer; The heat-sealable resin layer contains polyester, An exterior material for an electricity storage device, wherein at least a portion of the polyester is formed from a raw material derived from biomass. Item 2. The exterior material for an electricity storage device according to Item 1, wherein the polyester contains polybutylene terephthalate, at least a portion of which is formed from a raw material derived from biomass. Item 3. The polybutylene terephthalate has at least a terephthalic acid residue and a 1,4-butanediol residue, Item 3. The exterior material for an electricity storage device according to Item 2, wherein at least a portion of the terephthalic acid residues and the 1,4-butanediol residues are derived from biomass. Item 4. The exterior material for an electricity storage device according to Item 3, wherein at least a portion of the 1,4-butanediol residues are derived from biomass. Item 5. The exterior material for an electricity storage device according to Item 3 or 4, wherein at least a portion of the terephthalic acid residue is derived from a fossil fuel. Item 6. The exterior packaging material for an electricity storage device according to any one of Items 1 to 5, wherein a ratio of biomass-derived carbon as determined by radiocarbon (C14) measurement to the total carbon in the heat-sealable resin layer is 1% or more. Item 7. The exterior material for an electricity storage device according to any one of Items 1 to 6, wherein the barrier layer is made of an aluminum alloy foil or a stainless steel foil. Item 8. The exterior material for an electricity storage device according to any one of Items 1 to 7, further comprising an adhesive layer between the base layer and the barrier layer. Item 9. The packaging material for an electricity storage device according to any one of Items 1 to 8, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer. Item 10. The method includes a step of obtaining a laminate in which at least a base layer, a barrier layer, and a heat-sealable resin layer are laminated in this order from the outside, The heat-sealable resin layer contains polyester, A method for producing an exterior material for an electricity storage device, wherein at least a part of the polyester is formed from a raw material derived from biomass. Item 11. An electricity storage device, in which an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a package formed from the exterior material for an electricity storage device according to any one of Items 1 to 9. Item 12. A heat-sealable film for use in a heat-sealable resin layer of an exterior material for an electricity storage device, the heat-sealable resin layer being formed from a laminate having, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The heat-sealable film contains polyester, At least a part of the polyester in the film for a heat-sealable resin layer is formed from a raw material derived from biomass. [Explanation of symbols]
[0198] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Surface coating layer 10. Exterior materials for power storage devices
Claims
1. The laminate includes, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The heat-sealable resin layer contains polyester, An exterior material for an electricity storage device, wherein at least a portion of the polyester is formed from a raw material derived from biomass.
2. The exterior material for an electricity storage device according to claim 1 , wherein the polyester contains polybutylene terephthalate, at least a portion of which is formed from a raw material derived from biomass.
3. The polybutylene terephthalate has at least a terephthalic acid residue and a 1,4-butanediol residue, The exterior material for an electricity storage device according to claim 2, wherein at least a portion of the terephthalic acid residues and the 1,4-butanediol residues are derived from biomass.
4. The exterior material for an electricity storage device according to claim 3, wherein at least a portion of the 1,4-butanediol residues are derived from biomass.
5. The exterior material for an electricity storage device according to claim 3 or 4, wherein at least a part of the terephthalic acid residue is derived from a fossil fuel.
6. The exterior material for an electricity storage device according to any one of claims 1 to 4, wherein a ratio of biomass-derived carbon determined by radioactive carbon (C14) measurement to total carbon in the heat-sealable resin layer is 1% or more.
7. The electrical storage device packaging material according to any one of claims 1 to 4, wherein the barrier layer is made of an aluminum alloy foil or a stainless steel foil.
8. The exterior material for an electricity storage device according to any one of claims 1 to 4, further comprising an adhesive layer between the base material layer and the barrier layer.
9. The packaging material for an electricity storage device according to any one of claims 1 to 4, further comprising an adhesive layer between the barrier layer and the heat-sealable resin layer.
10. The method includes a step of obtaining a laminate in which at least a base layer, a barrier layer, and a thermally adhesive resin layer are laminated in this order from the outside, The heat-sealable resin layer contains polyester, A method for producing an exterior material for an electricity storage device, wherein at least a portion of the polyester is formed from a raw material derived from biomass.
11. An electricity storage device, comprising: an electricity storage device element including at least a positive electrode, a negative electrode, and an electrolyte; and the electricity storage device element is housed in a package formed from the exterior material for an electricity storage device according to any one of claims 1 to 4.
12. A heat-sealable film for use in a heat-sealable resin layer of an exterior material for an electricity storage device, the heat-sealable resin layer being formed from a laminate including, in order from the outside, at least a base layer, a barrier layer, and a heat-sealable resin layer, The heat-sealable film contains polyester, At least a part of the polyester in the film for a heat-sealable resin layer is formed from a raw material derived from biomass.
Citation Information
Patent Citations
Polyester container and its manufacturing method
JP2002512304A
Layered package material, outer package material for battery, and the battery
JP2008287971A
Method for producing polybutylene terephthalate
JP2014012822A
